Fibrinogen glycosylation and glycation: molecular insights into thrombosis and vascular disease - Borghi, Serena; Nencini, Francesca; Giurranna, Elvira; Barbaro, Ilenia; Taddei, Niccolò; Fiorillo, Claudia; Becatti, Matteo (Frontiers in Molecular Biosciences, 2025)
Fibrinogen, a key protein in blood coagulation, undergoes two distinct post-translational modifications (PTMs): glycosylation and glycation. Glycosylation is an enzymatic, tightly regulated process, whereas glycation occurs non-enzymatically under hyperglycemic conditions. Emerging evidence highlights the role of these modifications in cardiovascular risk. This review provides a comprehensive overview of how fibrinogen glycosylation and glycation contribute to altered haemostatic profiles and increased cardiovascular risk. Evidence is presented from inherited fibrinogen disorders, liver disease, diabetes, and chronic conditions such as end-stage renal disease. Additionally, the potential use of glycosylation and glycation patterns as diagnostic or prognostic biomarkers in cardiovascular disease is discussed. Overall, changes in fibrinogen’s glycosylation and glycation profiles may serve as important markers for cardiovascular risk assessment in many diseases, offering insights into the molecular mechanisms underlying these conditions.